Frequency of Residential Irrigation Maintenance Problems - Thomas R. Olmsted; Michael D. Dukes (EDIS)
The majority of Florida in-ground irrigation systems have some type of maintenance problem that could be causing excessive water use. Inspections should be done on a regular basis. This factsheet describes the five residential irrigation problems that represented half of the problems found in 3,416 audits by Urban Mobile Irrigation Labs in Florida. This 7-page fact sheet was written by Thomas R. Olmsted and Michael D. Dukes and published by the UF Department of Agricultural and Biological Engineering, January 2011.